1985
DOI: 10.1007/bf01415508
|View full text |Cite
|
Sign up to set email alerts
|

Drag reduction experiments with very large pipes

Abstract: Various substances have been tested in the laboratory for their suitability as flow enhancers in aqueous solutions. The following maximum drag reductions (%) were obtained with pipes of 14 mm diameter and a Reynolds number of 10s: Na-carboxy methylcellulose (32), hydroxyethyl cellulose (42), cetyltrimethylammonium chloride/ cr-naphthol (74; Re = 104), polyethylene oxide (76), K-polyphosphate/Na-pyrophosphate (77), polyacrylamide (80). The tested, partially hydrolysed polyacrylamide which was produced by a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Two-component LDV measurements were conducted by many researchers. [17][18][19][20][21] All these experiments confirmed that the root mean square of the velocity fluctuations in the streamwise direction increases while the rms of the fluctuations in the wall-normal direction decreases with DR, and the Reynolds shear stress decreases in the drag-reducing flows. The sum of Reynolds shear stress and viscous shear stresses is lower than the total shear stress without the presence of polymer agents.…”
Section: Introductionsupporting
confidence: 56%
“…Two-component LDV measurements were conducted by many researchers. [17][18][19][20][21] All these experiments confirmed that the root mean square of the velocity fluctuations in the streamwise direction increases while the rms of the fluctuations in the wall-normal direction decreases with DR, and the Reynolds shear stress decreases in the drag-reducing flows. The sum of Reynolds shear stress and viscous shear stresses is lower than the total shear stress without the presence of polymer agents.…”
Section: Introductionsupporting
confidence: 56%
“…At low concentrations in straight pipe flows, DRPs show asymptotic DR immediately after transition from laminar to turbulent flow regime [93]. It has been reported that the presence of dissolved salts in solution reduces the effectiveness of the DRA in both straight pipes and curves [9,94]. Also adding starch to polymers is reported to have little or no effect on the frictional losses in curved pipes [9].…”
Section: Effect Of Pipe Diametermentioning
confidence: 99%
“…Drag reduction of very dilute solutions has been studied extensively (Virk 1975;McComb and Rabie 1982;Interthal and Wilski 1985;Bird et al 1987;Kulicke et al 1989;Tiu et al 1995Tiu et al , 1996Choi et al 2000;Jovanovic et al 2006), and it can be as high as 80%. These "dilute solutions" are characterized by very small polymer concentrations (several ppm) and a very small viscosification of the water (several %).…”
Section: Drag Reduction Coil/stretch Transition and Polymer Degradamentioning
confidence: 99%